The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/dom.12859
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of prednisolone‐induced hyperglycaemia in hospitalized patients: Insights from a randomized, controlled study

Abstract: There were no differences in the efficacy or safety of the isophane and glargine-based insulin regimens. We recommend an initial daily insulin dose of 0.5 units/kg bodyweight if not on insulin, a greater than 30% increase in pre-prednisolone insulin dose and larger insulin dose adjustments in patients with prednisolone-induced hyperglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
0
32
0
1
Order By: Relevance
“…Ruiz de Adana et al reported that in patients with type 2 diabetes and respiratory disease treated with methylprednisolone or deflazacort, there was no significant difference in glucose control between patients randomized to glargine-or isophane-based basal bolus insulin (39). Similarly, we reported no difference in mean glucose or hypoglycaemia in patients with hyperglycaemia with or without known diabetes while taking short-term prednisolone who were randomized to insulin glargine and insulin aspart vs insulin isophane and insulin aspart (30).…”
Section: Pharmacokinetics Of Insulin Therapy For Prednisolone-inducedmentioning
confidence: 42%
See 3 more Smart Citations
“…Ruiz de Adana et al reported that in patients with type 2 diabetes and respiratory disease treated with methylprednisolone or deflazacort, there was no significant difference in glucose control between patients randomized to glargine-or isophane-based basal bolus insulin (39). Similarly, we reported no difference in mean glucose or hypoglycaemia in patients with hyperglycaemia with or without known diabetes while taking short-term prednisolone who were randomized to insulin glargine and insulin aspart vs insulin isophane and insulin aspart (30).…”
Section: Pharmacokinetics Of Insulin Therapy For Prednisolone-inducedmentioning
confidence: 42%
“…Although there are plausible mechanisms by which short-term hyperglycaemia might increase morbidity and mortality, such as inducing endothelial dysfunction and oxidative stress (29), data on major clinical endpoints are lacking. In our study, the inclusion criteria for hypoglycaemic therapy were one blood glucose level above 15 mmol/L or two blood glucose levels above 10 mmol/L within 24 h, to ensure subjects had either marked or sustained hyperglycaemia (30).…”
Section: Is Treating Hyperglycaemia During Acute Prednisolone Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Aunque se ha aducido que el uso de NPH podría asociarse a un menor riesgo de hipoglucemias frente a insulina glargina o detemir 17 , en nuestro estudio, basado en una terapia basal-bolo, solo hubo una hipoglucemia grave en el grupo del PC, a pesar de las altas dosis de insulina administrada. Radhakutty et al, en su análisis de control glucémico los días 1 y 3 del ingreso aplicando una pauta basal-bolo versus insulina NPH, no observaron diferencias significativas ni en el control glucémico ni en la incidencia de hipoglucemias 19 . Otros estudios también han encontrado una eficacia similar entre NPH y pauta basal-bolo 16,18 .…”
Section: Discussionunclassified